1990
DOI: 10.1126/science.2237429
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of an Immediate-Early Inducible Gene as a Mechanism for B Cell Tolerance Induction

Abstract: Stage-specific gene regulation is important in determining cell function during development. Immature B cells expressing membrane-bound immunoglobulin M (mIgM) are sensitive to antigen-induced tolerance, whereas mature B cells are activated by antigen. Previous studies have established an association between Egr-1 gene induction and antigen receptor (mIgM)-mediated activation of mature B cells. Here it is shown that the immature B cell line WEHI-231 and tolerance-sensitive bone marrow-derived B cells do not ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 27 publications
(26 reference statements)
1
45
0
Order By: Relevance
“…We have chosen the induction of the Krox-24 gene as an endpoint because the activation of MAPK has been correlated with an increase in its transcription [38] and also because its induction is a ubiquitous correlate of mitogenic stimulation [39]. Krox-24 expression is independent of protein synthesis and appears within minutes of mitogenic stimulation [40,41]. Our results showed a massive accumulation of Krox-24 protein on stimulation with NT in both CHO-hNTR and HT29 cells.…”
Section: Ntr Stimulation Induces Krox-24 Gene Expressionmentioning
confidence: 99%
“…We have chosen the induction of the Krox-24 gene as an endpoint because the activation of MAPK has been correlated with an increase in its transcription [38] and also because its induction is a ubiquitous correlate of mitogenic stimulation [39]. Krox-24 expression is independent of protein synthesis and appears within minutes of mitogenic stimulation [40,41]. Our results showed a massive accumulation of Krox-24 protein on stimulation with NT in both CHO-hNTR and HT29 cells.…”
Section: Ntr Stimulation Induces Krox-24 Gene Expressionmentioning
confidence: 99%
“…Alternatively, perhaps the IEG proteins present basally are not active, and their activation requires post-translational modifications (phosphorylation, demethylation, etc.) (Seyfert et al, 1990). A previous report suggested that Zif268 may play a role in spontaneously maintaining the inhibitory output of GABAergic neurons in the striatum (Ishida et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Seyfert et al [59] have provided an interested suggestion. B cell lines representative of mature and immature B cells exist, and both can have their Ig receptors cross-linked by anti-p heavy-chain antibodies, but whereas this results in a positive growth response in the mature B cell line, a negative, growth-inhibitory signal is delivered to the immature line resulting in eventual cell death.…”
Section: Clonal Abortion and Clonal Anergy In B Lymphocyte Tolerancementioning
confidence: 99%